Outlooking the Future with Nanosciences and Nanotechnology and Their Applications - Filipe, José António; Ferreira, Manuel Alberto M. (Contemporary Perspective on Science, Technology and Research Vol. 7, 2024)
The small world of matter is getting smaller and smaller. Nano sciences in recent years had huge developments allowing nanotechnologies to take enormous steps in the development of materials and processes. Numerous applications in a wide scope of fields are very beneficial for humans, and much research in development is very promising. Applications in medicine, industry, electronics, energy, or aeronautics are only some examples of areas where enormous benefits exist, and potentialities are clear. Some nanotechnologies are already applied, and others are in development or testing phases.